SPOSOBNOSTI NOGOMETAŠA - JUNIORA PREMIJER LIGE U PROSTORU KONATIVNIH KARAKTERISTIKA - Midhat Mekić; Šener Bajramović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
In accordance with the basic purpose of this research, the predictive infl uence of the chosen variables of the connate sphere has been evaluated applying the regressive analyses. It has been evaluated through successful results in the basic-motional and situation-motional tests used as a criteria and applied on the specimen of the B&H Premier League of the junior football players. The result showing the connectivity of the entire system of the manifest variables of the connate sphere and the successful performance of the basicmotional and situation-motional tests, is explained through the multiple correlation coeffi cient Ro=.87. This further explains approx. 59% of the common variability of the predictive system (variables to evaluate aggression, moral, anxiety and inferiority at the selected specimen of the examinees) and the criteria variables (tests to evaluate the basic motional and specifi c motional abilities).